Management of energy renovation for traditional rural residential houses - Szarejko, Magdalena (Budownictwo i Architektura, 2024)
Energy renovation aims to reduce a building's energy consumption by improving the thermal properties of building partitions and enhancing the efficiency of installation systems. This is an essential component in achieving the climate goals set by the international community. Renovating buildings of cultural value requires preserving architectural features that define their recognisability, which significantly complicates and limits the choice of methods and materials. In Poland, this process typically involves partial thermal modernisation, addressing selected elements of the building alongside the replacement of the heating source. This approach results in only a minor reduction in energy loss and a considerable loss of architectural value. This study assesses the feasibility of implementing comprehensive energy renovation management at the local level to improve the protection and preservation of traditional brick buildings, which are an architectural hallmark of the Pomeranian countryside. A model for an integrated energy renovation management system was proposed, drawing on European solutions and analysing their adaptability to national specificities. The complexity of the issue is highlighted, and the article recommends considering the entire life cycle of the building in the renovation management process: from findings on planning, design, and implementation solutions to monitoring energy performance during operation.